A noninterventional study evaluating the effectiveness and safety of lacosamide added to monotherapy in patients with epilepsy with partial‐onset seizures in daily clinical practice: The VITOBA study. (3rd November 2015) - Runge, Uwe; Arnold, Stephan; Brandt, Christian; Reinhardt, Fritjof; Kühn, Frank; Isensee, Kathleen; Ramirez, Francisco; Dedeken, Peter; Lauterbach, Thomas; Noack‐Rink, Matthias; Mayer, Thomas
Summary: Objective: Evidence for the efficacy and safety of adjunctive lacosamide in the treatment of partial‐onset seizures (POS) was gained during placebo‐controlled clinical trials in patients with treatment‐resistant seizures who were taking one to three concomitant antiepileptic drugs (AEDs). The VITOBA study (NCT01098162) evaluated the effectiveness and tolerability of adjunctive lacosamide added to one baseline AED in real‐world clinical practice. Methods: We conducted a 6‐month observational study at 112 sites across Germany. Adult patients (≥16 years) with POS received lacosamide adjunctive to only one baseline AED. Seizure frequency reduction at the end of the observation period was compared with a 3‐month retrospective baseline period. Results: Five hundred seventy‐one patients received lacosamide at least once (Safety Set [SS]); 520 provided evaluable seizure records (Full Analysis Set [FAS]); and 499 took in‐label dosages of lacosamide (up to 400 mg) and were evaluated for effectiveness (modified FAS). Median baseline seizure frequency was 2.0 per 28 days: 47.1% of patients (235/499, mFAS) took a concomitant sodium channel–blocking (SCB) AED; 38.1% (190/499) had only one lifetime AED; and 18.4% (92/499) were aged ≥65 years (mFAS). At the final visit, 72.5% (358/494) of patients showed a ≥50% reduction in seizure frequency from baseline, 63.8% (315/494) showed a ≥75% reduction, and 45.5% (225/494) were seizure‐free. Seizure freedom rates were higher in patients aged ≥65 years (56.7%) compared with patients aged <65 years (43.1%), in patients with ≤5 years epilepsy duration (52.5%) versus >5 years duration (41.0%), and when added to first monotherapy (60.5%) rather than as a later therapy option. Treatment‐emergent adverse events (TEAEs) were reported by 48.5% (277/571) of patients (SS), with a profile similar to that observed in pivotal trials; 466 of patients (81.6%, SS) continued lacosamide therapy after the trial. Significance: These results suggest that lacosamide use, added to one concomitant AED, was effective at improving seizure control and was well tolerated in patients treated in routine clinical practice.